(untitled) (Italian Review of Legal History, 2021)
Only a small number of chartae drawn up since the early Middle Ages can be said to have had a parallel life to their usual and pre-eminent legal or notarial destination. This parallel life follows the choice, mainly by legatees, to engrave onto stone even just part of the textual content of the parchments. The purpose of this decision was to notify, publicise, and perpetuate, generally pro redemptione animae, the memory of what wealthy benefactors had arranged, initially in favour of monastic institutions and, later, also in favour of both religious and secular charitable institutions. Most of these scarce inscriptions, which we classify as ‘chartae lapidariae’ – due to their close relationship to notarial chartae, from which they derive – have been produced in Italy since the end of the tenth century, to be regularly exhibited inside or nearby sacred places. In most cases, we speak of inscriptions containing inter vivos or mortis causa testamentary acts or donations; less often, their enacting and probative content refers to papal bulls, decrees or royal or imperial orders. In both instances, we are faced with engraved documents which are irrefutable from a legislative point of view. However, the customary loss of the notarial document from which each charter derives and the lack of one or more of its essential elements, such as the datatio – probably due to the charter’s generally accepted function, since Roman times, as ‘regesta’ of the original document – means that the chartae lapidariae can hardly be considered ‘documents in the proper sense’, but only separate epigraphic ‘monuments’. Therefore, they are particularly interesting to analyse merely for their historical significance. Despite this, due to all the elements considered up to now – which can be summarised as the difficulty of demonstrating the reliability of the contents engraved onto stone, given that it is impossible to reconstruct the intimate epigraphic/documentary use of the lapidary chartae in relation to their lost notarial original – the work of Pietro Sella, Cinzio Violante, and Ottavio Banti in the past century has shed an important light on this type of documents. Nonetheless, even today, the chartae lapidariae receive little consideration. However, in the face of documentary scarcity – as is the case for Milan – they are effective in defining the role of the laity, both within the ecclesial space and in society. They are also useful in the study of charitable institutions – religious as well as secular – and of the ruling classes of Italy, especially of Milan, during the eleventh century. Therefore, despite the fact that the diplomatic significance, itself limiting the legal reliability of the chartae lapidariae, seems to have often prevailed over the historical interest, albeit of an analytical nature of the contents of the chartae, this work aims at drawing the attention to three important and exceptional examples produced during the last twenty years of the eleventh century in Viterbo, Milan and Collescipoli.